Obesity and the Development of Lung Fibrosis - Guo, Xia; Sunil, Christudas; Qian, Guoqing (Frontiers in Pharmacology, 2022)
Obesity is an epidemic worldwide and the obese people suffer from a range of respiratory complications including fibrotic changes in the lung. The influence of obesity on the lung is multi-factorial, which is related to both mechanical injury and various inflammatory mediators produced by excessive adipose tissues, and infiltrated immune cells. Adiposity causes increased production of inflammatory mediators, for example, cytokines, chemokines, and adipokines, both locally and in the systemic circulation, thereby rendering susceptibility to respiratory diseases, and altered responses. Lung fibrosis is closely related to chronic inflammation in the lung. Current data suggest a link between lung fibrosis and diet-induced obesity, although the mechanism remains incomplete understood. This review summarizes findings on the association of lung fibrosis with obesity, highlights the role of several critical inflammatory mediators (e.g., TNF-α, TGF-β, and MCP-1) in obesity related lung fibrosis and the implication of obesity in the outcomes of idiopathic pulmonary fibrosis patients.